Constructing Civil Liberties : Discontinuities in the Development of American Constitutional Law. - Kersch, Ken I. (Cambridge University Press, 2004)
This book is a revisionist account of the development of the Supreme Court's modern civil liberties and civil rights jurisprudence. It explains that jurisprudence is the outgrowth of a sequence of highly particular progressive-reformist ideological currents, that formed the modern American state.